Advanced surgical techniques and considerations in carotid body tumor management: insights from a cohort study - Farooq Ahmad Ganie; Masarat-ul Gani; Hakeem Zubair Ashraf; Shahbaz Bashir; Iqra Nazir Naqash; Mudasir Hamid Bhat; Shadab Maqsood; Altaf Hussain Mir; Mohd Iqbal Dar (Egyptian Journal of Neurosurgery)
Abstract Background Carotid body tumors (also known as glomus tumors) represent the most prevalent paragangliomas found in the head and neck region. These neoplasms originate from the aggregation of chemoreceptor cells in the cervical area, stemming from the neural crest during embryonic development. Aims and objectives This study aims to delineate our singular institutional experience concerning the clinical characteristics, surgical strategies, and outcomes associated with carotid body tumors (CBTs). Materials and methods Surgical intervention was administered to a cohort of 40 patients. Among them, 7 individuals were classified as Shamblin Type 1, 20 as Type 2, and 13 as Type 3. Only one patient necessitated a saphenous vein interposition graft for the right internal carotid artery. For Shamblin Type 3 lesions, we employed the RF (Rija-farooq) technique, a retrograde dissection method wherein we first delineated the tumor from the internal carotid artery, followed by the external carotid artery, and finally, at the carotid bifurcation. Results Notably, none of the patients exhibited any postoperative neurological or vascular complications. Furthermore, during the subsequent follow-up period, no instances of tumor recurrence or mortality were recorded. Conclusion Surgical resection stands as the optimal therapeutic approach for managing CBTs. Once the diagnosis of CBT is confirmed, prompt surgical intervention should be pursued. Essential considerations in treatment planning include meticulous assessment of imaging characteristics and cerebral collateral circulation, which guide the selection of appropriate surgical methods.